The Effect of Storyline Therapy on The Development Language in 3 Years Age Children - Erni Agit Ekawati; Ema Alasiry; Marni Br Karo; Andi Nilawati Usman; Titus Tambaip (JURNAL KEBIDANAN, 2023)
Delays or disorders in children's speech and language in Indonesia are increasingly common, parents must be aware of their child's speech development, remembering that if these delays are not treated early, they will result in intelligence and behavioral disorders. The aim of this research is to determine the effect of storytelling therapy on language development in 3-year-old children at Posyandu Arumsari III Puskesmas Mranggen I. This type of research is a quantitative, quasi-experimental design type One Group Pretest Posttest design. The population of this study was all children under 3 years old at the Posyandu Arumsari III, Desa Kembangarum, Puskesmas Manggen 1, Kabupaten Demak, with a total of 26 children. The sample is determined by Federer's formula of 18 respondents. The sampling technique in this research is purposive sampling. Data analysis used univariate and bivariate analysis using Wilcoxon. Language development in children 3 years before storytelling therapy had an average of 29.2, with a median 29, after storytelling therapy had an average of 30.67, median 31. There was an effect of storytelling therapy on language development in children aged 3 years, obtained Pvalue 0.002 0.05. There is an effect of storytelling therapy on language development in children aged 3 years. The results of this study are expected that mothers can do storytelling therapy at least 3 times a week to stimulate children's language development.